Enzymatic Decolorization of Anthraquinone and Diazo Dyes Using Horseradish Peroxidase Enzyme Immobilized onto Various Polysulfone Supports - Celebi, Mithat; Kaya, Mehmet Arif; Altikatoglu, Melda; Yildirim, Huseyin (SPRINGER, 2013)
In this study, covalent immobilization of the horseradish peroxidase (HRP) onto various polysulfone supports was investigated. For this purpose, different polysulfones were methacrylated with methacryloyl chloride, and then, nonwoven fabric samples were coated by using solutions of these methacrylated polysulfones. Finally, support materials were immersed into aquatic solution of HRP enzyme for covalent immobilization. Structural analysis of enzyme immobilization onto various polysulfones was confirmed with Fourier transform infrared spectroscopy, atomic force microscopy, and proton nuclear magnetic resonance spectroscopy. Decolorization of textile diazo (Acid Black 1) and anthraquinone (Reactive Blue 19) dyes was investigated by UV-visible spectrophotometer. Covalently immobilized enzyme has been used seven times in freshly prepared dye solutions through 63 days. Dye decolorization performance of the immobilized systems was observed that still remained high (70 %) after reusing three times. Enzyme activities of immobilized systems were determined and compared to free enzyme activity at different conditions (pH, temperature, thermal stability, storage stability). Enzyme activities of immobilized systems and free enzyme were also investigated at the different temperatures and effects of temperature and thermal resistance for different incubation time at 50 A degrees C. In addition, storage activity of free and immobilized enzymes was determined at 4 A degrees C at different incubation days.
Keywords: Decolorization; Horseradish peroxidase; Immobilized enzyme; Polymer support; Polysulfone; Textile dyes; WASTE-WATER; TEXTILE; REMOVAL; TEMPERATURE; MEMBRANES; EFFLUENT; AZO; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology